Mechanical properties of sugar palm fibre-reinforced epoxy composites - Leman, Zulkiflle (2009)
The potential use of natural fibres as substitutes to synthetic fibres (glass in particular) is of great interest due to growing global environmental and social concern, uncertainties in the supply and price of petroleum based products, and new environmental regulations that have forced the search for renewable green materials, which are compatible with the environment. In addition, glass fibres can also cause acute irritation to the skin, eyes and upper respiratory tract if one is being exposed to their use for a prolonged period of time. The goal of this study was to explore the possibility of using the sugar palm (Arenga pinnata) fibres as the reinforcement material in epoxy matrix. The mechanical performances of composite materials strongly depend on the nature and orientation of the fibre, the nature of the matrix and the quality of adhesion between the two constituents. One of the biggest challenges for natural fibres is the ability for moisture repellence. Therefore, tests were conducted to study the moisture absorption behaviour of the epoxy resin and also the composites. Test results showed that sugar palm fibre epoxy composite absorbed about 0.93% moisture after being immersed in water for 33 days. Another challenge was to understand the degree of adhesion between the fibre and matrix. The surface properties of the sugar palm fibre were modified using ‘biological’ treatments. In this study sea water, fresh (pond) water and sewage water were used as treatment agents. This led to biological, chemical and water degradation to the sugar palm fibre. Interfacial shear strengths were studied using the single fibre pull out test and the results showed that the fibres treated with sea water exhibited the strongest fibrematrix bonding. Morphological and structural changes of the fibres were investigated using scanning electron microscope (SEM). It was found that the biological treatments had modified the surface properties of the sugar palm fibre thus resulted in a better adhesion quality as compared to the untreated fibre. A series of mechanical tests namely tensile, flexural and impact were conducted on the composites with 10%, 15%, 20% and 30% (by volume) of randomly short chopped fibres. The results showed that the strengths increased with increased fibre loadings of up to 20% but the composite with 30% fibre content showed the opposite behaviour.